RANCANG BANGUN MESIN PENGIRIS KACANG TANAH UNTUK TOPPING PEYEK - Angga Triatmaja; Muhammad Darmawan; Talsa Fani; Idiar Idiar; Erwansyah Erwansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Peyek is one of the typical Javanese snacks made from rice flour dough made from peanuts and other ingredients. The results of a survey that was carried out at Mr. Cahyo's residence were slicing 3 kg of peanuts per three days which was carried out with two slicing processes to obtain small slices. The obstacle faced by Mr. Cahyo is the slicing of peanuts which still uses manual tools from wood, where on the big day Mr. Cahyo requires 100 kg of peanuts to be sliced, so it takes a lot of time to finish. The purpose of the design of this peanut slicing machine is to produce thick slices with a size of 3-5 mm in one slicing process. The stages of implementing this final project consist of stages of data collection, planning, calculation analysis, manufacturing process, assembly process, and conducting trials. The result of the design of this machine is that the dimensions of the machine are 300×300×405 mm, and from the trial of this peanut slicing machine, the results are 3-5 mm thick slices, and the data obtained for slicing 500 grams of peanuts takes about 1 minute.